OPTIMASI SUHU PENYIMPANAN SAMPEL URIN TERHADAP ANALISIS KANDUNGAN METAMFETAMIN SERTA METABOLITNYA DENGAN GC-MS - Mahmudi, I.; Suaniti, N. M.; Diantariani, N. P. (Jurnal Kimia (Journal of Chemistry); Vol. 17, No.1, Januari 2023, 2023)
Suhu penyimpanan sangat mempengaruhi hasil analisis sampel metamfetamin menggunakan kromatografi gas dan spektroskopi massa. Optimasi suhu penyimpanan terhadap analisis metamfetamin serta metabolitnya dengan kromatografi gas dan spektroskopi massa telah dilakukan dengan tujuan untuk membandingkan hasil pembacaan dan kadar senyawa metamfetamin pada sampel urin yang berbeda. Sampel urin normal, sampel urin normal yang ditambahkan sabu-sabu, dan sampel urin pengguna masing-masing dikumpulkan sebanyak 60 mL. Hasil uji pendahuluan menunjukkan sampel urin normal negatif MA, sampel urin normal yang ditambahkan sabu-sabu dan sampel urin pengguna sabu-sabu positif MA, kemudian masing-masing sampel dibagi tiga kelompok untuk analisis langsung dan disimpan dalam suhu 4 dan 25 o C selama 14 hari. Hasil analisis dengan kromatogarfi gas, pada kromatogram sampel urin normal tidak terdeteksi adanya serapan senyawa MA maupun metabolitnya hanya muncul serapan seperti 9-octadecenamide, hexadecanamide, dodecanamide, dan tetradecanamide yang merupakan puncak serapan dari lemak essensial. Sementara pada kromatogram sampel urin normal yang ditambahkan sabu-sabu dan sampel urin pengguna muncul puncak senyawa MA pada Rt 5,27-5,28 tetapi metabolit MA yaitu amfetamin hanya muncul pada kromatogram sampel urin pengguna yaitu pada Rt 5,07-5,08. Data hasil analisis kromatografi gas didukung oleh data pecahan m/z 44, 58, 91, dan 134 yang merupakan pecahan khas senyawa MA dan m/z 44, 65, 91, dan 120 yang menunjukkan pecahan khas amfetamin. Suhu 4 o C merupakan suhu optimum dalam penyimpanan sampel urin pengguna sabu-sabu area tidak terjadi penurunan kadar MA yang signifikan. Kata kunci : Amfetamin, gas kromatografi, metamfetamin, sampel urin,  spektroskopi massa. ABSTRACT         The storage temperature of the methamphetamine samples has significantly influenced the analysis results of the samples using gas chromatography and mass spectroscopy. Optimization of the storage temperature for analysis of the methamphetamine and its metabolites by gas chromatography and mass spectroscopy has been done aiming to compare the level of methamphetamine compound in different urine samples. Normal urine samples, normal urine samples added with methamphetamine, and urine samples of the methamphetamine users were each collected as much as 60 mL. The result of the methamphetamine-screening test showed that the normal urine samples were negative but the normal urine samples added with methamphetamine and urine samples of the methamphetamine users were positive. Each sample was then divided into three groups for direct analysis and stored at 4 and 25 o C for 14 days. The methamphetamine analysis using gas chromatography showed that the chromatogram of the normal urine samples did not show any absorption of methamphetamine or its metabolites. Still, the absorption of 9-octadecenamide, hexadecanamide, dodecanamide, and tetradecanamide was detected, which were the absorption peaks of essential fats. Meanwhile, the chromatogram of the normal urine added with methamphetamine and the urine samples of the methamphetamine users indicated the peak of methamphetamine compound detected at Rt 5.27-5.28, however, the amphetamine (methamphetamine’s metabolite) peak was only detected at the chromatogram of the urine samples of the methamphetamine user, which was at Rt 5.07-5.08. The data of the gas chromatography analysis were supported by the fraction of m/z 44, 58, 91, dan 134 which were typical fractions of methamphetamine, and  m/z 44, 65, 91, dan 120 were typical fractions of amphetamine. The results showed that the temperature of 4 o C was the optimum temperature for storing urine samples of methamphetamine users because there was no significant decrease in methamphetamine levels. Keywords : Amphetamine, gas chromatography, mass spectroscopy, methamphetamine, urine sample.